Synergistic Effect of the Fuel Microemulsion Characteristics on Drop Interaction with a Hot Wall; Energy & Fuels; Vol. 35, iss. 9 - Ashikhmin A. E. Alexander Evgenjevich; Khomutov N. A. Nikita Andreevich; Piskunov M. V. Maksim Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Yanovsky V. A. Vyacheslav Aleksandrovich (2021, 2021)
Title screen